Incorporation of probiotics (Bifidobacterium animalis subsp. Lactis) into 3D printed mashed potatoes: Effects of variables on the viability. (February 2020) - Liu, Zhenbin; Bhandari, Bhesh; Zhang, Min
Graphical abstract: Highlights: Probiotics was incorporated in 3D printed mashed potatoes. Effect of printing factors on probiotics viability was firstly studied. 3D printability was correlated with rheological properties. A new form of starch-based probiotic functional food was developed. Abstract: 3D printing is an emerging technology with the potential to revolutionize people's eating habits. This study firstly optimized the mashed potatoes (MP) formulation and correlated its 3D performance with rheological properties. Yield stress and consistency index ( K ) were closely related with MP's extrusion behavior, and too high values of them (like 2558 Pa and 2794 Pa·s n ) caused the difficulty in extrusion process. Yield stress and elastic modulus (G′) were critical to MP's self-supporting performance and too low values of them resulted in the deformation of printed parts during storage. The feasibility of incorporation of probiotics ( Bifidobacterium animalis subsp. Lactis BB-12 ) into 3D printed mashed potatoes (MP) was then studied. MP with probiotics was printed with different nozzle diameter (0.6, 1.0 and 1.4 mm), printing temperature (25, 35, 45 and 55 °C) and evaluated for survival during extrusion and storage at 5 °C. It was found only the small nozzle diameter (0.6 mm) resulted in the reduction of probiotic viability from 9.93 log CFU/g to 9.74 log CFU/g. Greater reduction of viable counts of probiotics (from 10.07 log CFU/g to 7.99 log CFU/g) was found when the MP was held in a heating nozzle barrel at 55 °C for 45 min. No significant difference of probiotics viability in 3D printed samples was found during 12-day storage period at 5 °C. This study provides a new dimension on the development of functional foods by 3D printing.